Los cardos y las tareas rurales en la provincia de Buenos Aires durante el siglo XIX - Recalt, Gustavo (Centro de Historia Argentina y Americana, 2004)
In this paper, we focuses on the thistles and their influence on the rural works during the twentieth century, from the following items: the thistles' localization on the Buenos Aires province; their way of multiplication; which is the connection between the thistles and the men and animals; the thistles' influence on the management of colonial estancia. Contrary to the historiography, we consider that the thistles didn't determinate the rural works, but this was related with the scarcity of workers.